2014
DOI: 10.1177/0884533614564996
|View full text |Cite
|
Sign up to set email alerts
|

Survey Study Assessing Attitudes and Experiences of Pediatric Registered Dietitians Regarding Blended Food by Gastrostomy Tube Feeding

Abstract: Interest in BFGT is largely parent-driven or explored as an option for children with tube feeding intolerance. Almost 80% of RDs using this feeding substrate report overall positive outcomes, but 28% indicate they want more information on using BFGT in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(130 citation statements)
references
References 11 publications
6
122
2
Order By: Relevance
“…Although outside of our inclusion criteria, a recent study has indicated that healthcare professionals report positive experiences when using a blended diet,20 and there is some evidence highlighting clinical improvements from a blended diet in an American study 3. Here a total of 33 children with mean age of 34 months were given a pureed by gastrostomy tube diet in an attempt to improve symptoms, nutrition and hydration.…”
Section: Resultsmentioning
confidence: 99%
“…Although outside of our inclusion criteria, a recent study has indicated that healthcare professionals report positive experiences when using a blended diet,20 and there is some evidence highlighting clinical improvements from a blended diet in an American study 3. Here a total of 33 children with mean age of 34 months were given a pureed by gastrostomy tube diet in an attempt to improve symptoms, nutrition and hydration.…”
Section: Resultsmentioning
confidence: 99%
“…BTF has continued in areas where CF is not widely available, and in limited patient populations in developed countries . However, interest in and use of BTF have recently increased substantially in developed countries and are largely driven by patients and caregivers . This development creates conflict between the desire to provide patient‐centered care and adherence to established healthcare policies.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these children will use commercial formulae (CF), there is an increasing interest by health professionals and carers in the use of blenderised food for tube-feeding (BFTF) 2 3. Recently, the British Dietetic Association (BDA) issued a policy statement, advising its members that BFTF is not recommended 4.…”
Section: Introductionmentioning
confidence: 99%